2009
DOI: 10.1111/j.1398-9995.2008.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence rate to inhaled corticosteroids and their impact on asthma control

Abstract: In all periods, there were statistically significant differences in adherence rates for maintaining or not maintaining the asthma control. Optimal asthma control entailed adherence rate higher than 80%. Strategies for reducing asthma morbidity should include a regular monitoring of adherence to inhaled steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
4
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 23 publications
5
113
4
2
Order By: Relevance
“…Only four (5%) children had uncontrolled asthma, one of which had poor adherence to ICS. In comparison to earlier studies of long-term adherence in childhood asthma [6,22], median adherence was remarkably high (87%) in our study cohort. Despite the overall high levels and associated limited variability of both adherence and asthma control, a significant and consistent association was found between the two variables.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Only four (5%) children had uncontrolled asthma, one of which had poor adherence to ICS. In comparison to earlier studies of long-term adherence in childhood asthma [6,22], median adherence was remarkably high (87%) in our study cohort. Despite the overall high levels and associated limited variability of both adherence and asthma control, a significant and consistent association was found between the two variables.…”
Section: Discussioncontrasting
confidence: 90%
“…In previous studies, substantially different levels of adherence needed to achieve asthma control were reported, ranging from 40-60% to .80% [6,22]. However, in these studies, a high prevalence of children with short-term asthma control despite low adherence to ICS was observed, suggesting ICS overtreatment of mild intermittent symptoms or asthma in clinical remission.…”
Section: Discussionmentioning
confidence: 90%
“…The most commonly used value is 80%. 20,56 Lasmar et al 57 showed 80% to be the threshold between controlled and uncontrolled asthma, whereas Schroeder et al 58 argued that an arbitrary cutoff value is meaningless and should be replaced with a continuous measure of adherence. In the articles included in this review, the cutoff value varied between 50 and 80%.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Poor adherence to ICSs has been estimated to account for up to 60% of asthma-related hospitalizations (10)(11)(12)(13)(14). Furthermore, it has been suggested that optimal asthma control entails adherence rates to medication treatment more than 75% of the time (15). To date, studies of adherence to asthma controller medications in realworld populations have focused on dispensing data.…”
mentioning
confidence: 99%